Characterization of tmt-opsin2 in Medaka Fish Provides Insight Into the Interplay of Light and Temperature for Behavioral Regulation - Zekoll, Theresa; Waldherr, Monika; Tessmar-Raible, Kristin (Frontiers in Physiology, 2021)
One of the big challenges in the study of animal behavior is to combine the molecular-level questions of functional genetics, typically performed in the lab, with meaningful combinations of environmental stimuli. Light and temperature are important external cues, influencing the behaviors of organisms. Thus, understanding the combined effect of light and temperature changes on wildtype versus genetically modified animals is a first step to understand the role of individual genes in the ability of animals to cope with changing environments. Many behavioral traits can be extrapolated from behavioral tests performed from automated motion tracking combined with machine learning. The acquired datasets, typically complex and large, can be challenging for subsequent quantitative analyses. Here we investigate medaka behavior of tmt-opsin2 mutants versus corresponding wildtypes under different light and temperature conditions using automated tracking combined with a convolutional neuronal network and a Hidden Markov model-based approach. The temperatures in this study can occur in summer versus late spring/early autumn in the natural habitat of medakafish. Under summer-like temperature, tmt-opsin2 mutants did not exhibit changes in overall locomotion, consistent with previous observations. However, detailed analyses of fish position revealed that tmt-opsin2 mutants spent more time in central locations of the dish, possibly due to decreased anxiety. Furthermore, a clear difference in location and overall movement was obvious between mutant and wildtypes under colder conditions. These data indicate a role of tmt-opsin2 in behavioral adjustment, at least in part depending on the season.